2007
DOI: 10.1177/1087724x07302585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contracting Out Engineering Services Over Time in a State Department of Transportation

Abstract: Perhaps the most prevalent form of privatization, in terms of incidents of its use, is contracting out for services. This is especially true in state departments of transportation (DOTs), which have seen a rapidly growing reliance on contracted professional services in recent years. With this growth has come a variety of managerial issues that speak to the efficacy of this mode of service production. In this article we identify and analyze these issues by first reviewing the literature on managing contracted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The results are consistent with the previous studies of Williamson (1981, 1986), gen and Kingsley (2007, and Lamothe, Lamothe, and Feiock (2008) that commonly consider transaction cost as a major criterion in contracting under uncertainty. gDOT and contractors have developed bilateral interdependency through a longterm contractual relationship because of increasing transaction costs.…”
Section: Stable Relationship: "Semi-institutionalization" Of Privatizsupporting
confidence: 94%
See 2 more Smart Citations
“…The results are consistent with the previous studies of Williamson (1981, 1986), gen and Kingsley (2007, and Lamothe, Lamothe, and Feiock (2008) that commonly consider transaction cost as a major criterion in contracting under uncertainty. gDOT and contractors have developed bilateral interdependency through a longterm contractual relationship because of increasing transaction costs.…”
Section: Stable Relationship: "Semi-institutionalization" Of Privatizsupporting
confidence: 94%
“…We found that there has been a steady stream of employees moving from the agency to contractors. as gen and Kingsley (2007) found, brain drain can often occur under outsourcing because of stronger incentives (e.g., salaries and flexible work schedule) in the private sector. Brain drain can contribute to a hollowing out effect, losing the agency's internal technical capacity and relying more on contractors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the lead public‐sector sponsor, as well as other levels of government that are involved, executing a PFI project typically involves hiring multiple firms to serve as independent financial, insurance, legal, and technical advisers throughout the procurement process that may subcontract work to other specialist firms (Grimsey and Lewis 2004; Reeves 2008). This advisory role has become particularly significant because governments have increasingly outsourced many aspects of the process of procuring transportation projects to private‐sector consultants and contractors (Gen and Kingsley 2007; U.S. Federal Highway Administration 2005).…”
Section: Pfi As a Project‐oriented Production Processmentioning
confidence: 99%
“…However, most of the studies have been case studies of one or a few highway agencies (DeHart-Davis & Kingsley, 2005;Gen & Kingsley, 2007;Lee & Kingsley, 2009;Ponomariov & Kingsley, 2008). Our study employs the results of a survey sent to all state DOTs in the United States to explore the effects of outsourcing on the cost and quality of services.…”
Section: Introductionmentioning
confidence: 99%